Identification of Arabidopsis and Thellungiella genes involved in salt tolerance by novel genetic system - Ábrahám, Edit (Acta Biologica Szegediensis, 2011)
High salinity is a major constraint to plant growth and development. Plants respond to environmental stresses by altering gene expression pattern via a complex signaling network. We developed a novel genetic system based on conditional cDNA overexpression to isolate genes involved in plant salt tolerance. Transformation-ready Arabidopsis and Thellungiella cDNA libraries cloned in a plant expression vector under control of an inducible promoter were used to transfer into Arabidopsis, where activation of the inserted cDNA can lead to conditional phenotypes. Transgenic lines were tested in different screens (germination assay, growth-survival test). Our genetic system was suitable to identify not only well-known genes coding for proteins involved in stress tolerance, but several novel regulatory genes were discovered. Line N33 shows estradiol-dependent salt tolerant germination. It has a single T-DNA insertion; the full length cDNA encodes an unknown protein. This gene was designated as Novel Salt Tolerance (NSTO). The Thellungiella library allowed large scale random interspecific gene transfer and subsequent identification of novel regulatory genes which control stress tolerance in halophyte species. Our data illustrate that application of inducible cDNA expression libraries provides an efficient tool for genetic identification and functional analysis of novel positive or negative regulators of plant salt tolerance.